ضوابط واليات تسوية المنازعات المترتبة عن عملية التقييم العقاري - بن طيبة صونية (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
يعتبر التقييم العقاري وسيلة تقنية تعتمد على أسس ومبادئ علمية قانونية للبحث في تحديد القيمة المالية للعقارات بكافة أشكالها وصولا إلى القيمة السوقية التقريبية للعقار محل التقييم، وهذا من خلال اتباع الطرق العلمية في عملية التحديد والتقييم، والمتمثلة بالأساس في معاينة العقار والمنطقة المحيطة به ودراسة سوق العقار بشكل تفصيلي، وذلك بهدف الوقوف على القيمة السوقية العادلة للعقار.، هذا ويعتبر موضوع التقييم العقاري من المواضيع الهامة باعتباره حجر الزاوية في دفع عجلة الاستثمار في مجال التنمية، لذلك فان الدراسة في هذا الاطار انتقلت من إشكالية مفادها التعرف على الضوابط والطرق التي تتحكم في عملية التقييم واليات تسوية النزاعات المترتبة عن عملية التقييم؟. وطبعا وللوصول الى نتائج الدراسة والمتمثلة بالدرجة الأولى في دور التقييم في دفع عجلة التنمية في المجال الاستثمار العقاري، تعين استعمال المنهج الوصفي والتحليلي. Abstract: Estate evaluation is a monetary tool based on legal scientific principles to determine the monetary value of estates in their various types to reach the approximate market value of the estate under evaluation. This is through scientific procedures in the process of determining and evaluation. The process covers consulting the estate and the surrounding region and studying the estate market in detail in order to determine the just market value. The topic is considered one of the most important since it is a cornerstone in boosting the investment in the domain of development. Therefore, the study in this frame started from a problematic aiming at defining the ways and regulations that govern the evaluation process and mechanisms of settling disputes resulting from it. We used the descriptive and analytical method to reach results of the study that are primarily about the role of evaluation in boosting the development in the domain of estate investments